An efficient software verification using multi-layered software verification tool - V. Gayetri Devi, S; Nalini, C; Kumar, N (International Journal of Engineering and Technology, 2018)
Rapid advancements in Software Verification and Validation have been critical in the wide development of tools and techniques to identify potential Concurrent bugs and hence verify the software correctness. A concurrent program has multiple processes and shared objects. Each process is a sequential program and they use the shared objects for communication for completion of a task. The primary objective of this survey is retrospective review of different tools and methods used for the verification of real-time concurrent software. This paper describes the proposed tool â€˜F-JAVAâ€™ for multithreaded Java codebases in contrast with existing â€˜FRAMA-Câ€™ platform, which is dedicated to real-time concurrent C software analysis. The proposed system is comprised of three layers, namely Programming rules generation stage, Verification stage with Particle Swarm Optimization (PSO) algorithm, and Performance measurement stage. It aims to address some of the challenges in the verification process such as larger programs, long execution times, and false alarms or bugs, and platform independent code verificationÂ Â